Upsport Aplikasi Pemenuhan Kebutuhan Olahraga Berbasis Android (Menu Massage) - Fahmi, Donny Anhar; Wiyanto, Agus; Purwadi, Purwadi; Hidayat, Rahmat (YLPK Mahardhika, 2023)
The background to this research is that sports carried out every day often result in sports injuries. Based on this, massage therapy is needed to treat injuries or to restore muscle fitness. The public needs a sports massage service center that provides services for sports enthusiasts through online applications. Among them is the availability of masseur sports massage. The general public's knowledge regarding sports massage, massage information makes someone withdraw from the intention of wanting to exercise but does not know the masseur information if an injury occurs. UpSport is an all in one sports application, which contains many sports features that society needs today, including the need for competent sports massage masseur information according to society's needs. This application makes it easy for someone to search for a sports massage therapist based on the nearest location, sport, license held and price or rates. The aim of this research is to create an Android application that makes it easier for people to find sports massage therapists. The research method used is development research (R&D). Data analysis techniques used in design and development research use qualitative and quantitative data. Qualitative data at the beginning of research design and development of qualitative data is more dominant than quantitative data. Qualitative data is obtained, for example, through observations and interviews during needs analysis. Quantitative data was obtained using a questionnaire and measured using a Likert scale. The output of this research is the UPSPORT application which has IPR and accredited journals. The results of the assessment carried out by researchers on users of the application